Cultivating the Interpersonal Domain: Compassion in the Supervisor-Doctoral Student Relationship - Lundgren, Oskar; Osika, Walter (Frontiers in Psychology, 2021)
The long-term and complex supervisor-doctoral student relationship is often characterised by tension and frictions. In higher education research, models and interventions that take the potential beneficial interpersonal effects of compassion into account seem to be scarce. Hence, the aim of this study was to conceptualise the potential role compassion could have in the cultivation of an affiliative and sustainable supervisor - doctoral student relationship. The concept of compassion was investigated and analysed in relation to a contemporary model of supervisor behaviours. Furthermore, a systematic literature search in the scientific databases PubMed, PsychInfo, ScienceDirect, and Google Scholar was performed. The conceptual analysis revealed that the interpersonal domain, in which compassion could afford a shared sense of warmth, is neglected in previous definitions. Furthermore, the integration of compassion into a model of adaptive supervisor behaviour indicates a strong case for a salutary role for compassion in the supervisor – doctoral student relationship. However, the literature review showed that empirical data are lacking and more studies are needed. The role of compassion deserves to be investigated empirically in this particular interpersonal context.